Kształcenie dzieci i młodzieży w Polsce w latach 70. XX wieku = Education of children and youth in 1970's Poland - Domke, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is concentrated on the sector of education, from kindergartens to high schools. It shows the role of education in the context of state propaganda and changes in its structure (realization of reform in education). Above all it concerned questions connected with plots concentrated on current stages of education of polish society. The article shows civilizational advance of polish nation in the area of education. It try to answer on the question: can we speak about a positive elements of prepared reform and was it only a copy of a soviet solutions upon that thing.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia